The Role of Financial Institutions in Controlling Inflation through Money Supply Policies in Indonesia in the Era of the COVID-19 Pandemic - Ita Wulandari; Linda Lidiyawati; Gama Pratama; Delia Apriyahya; Siti Nurkommala (Ecobankers : Journal of Economy and Banking, 2026)
The COVID-19 pandemic that has hit Indonesia since the beginning of 2020 has had a significant impact on national economic stability, especially in terms of controlling inflation and managing the money supply. This study aims to analyze the role of financial institutions, especially Bank Indonesia as a central bank and banking institution, in controlling inflation through money supply policies during the COVID-19 pandemic era. The research method used is a literature review study with empirical data analysis obtained from publications of Bank Indonesia, the Central Statistics Agency, and scientific journals for the period 2020-2024.The findings of the study indicate that Bank Indonesia has implemented a variety of accommodative monetary policy instruments, including the reduction of the BI 7-Day Reverse Repo Rate, the easing of the Minimum Mandatory Current Account, and the policy of purchasing Government Securities to maintain liquidity and stability of the financial system. Although the money supply has increased significantly during the pandemic period, inflation in Indonesia has remained under control within the set target range, even experiencing deflation in some periods. This shows the effectiveness of coordination between monetary and fiscal policies, as well as the active role of banking institutions in maintaining economic stability. The study concludes that financial institutions play a crucial role in controlling inflation through proper money supply management, although external challenges such as global price pressures and economic uncertainty remain to require continued vigilance.